2017
DOI: 10.1016/j.talanta.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Headspace single drop microextraction versus dispersive liquid-liquid microextraction using magnetic ionic liquid extraction solvents

Abstract: A headspace single drop microextraction (HS-SDME) method and a dispersive liquid-liquid microextraction (DLLME) method were developed using two tetrachloromanganate ([MnCl])-based magnetic ionic liquids (MIL) as extraction solvents for the determination of twelve aromatic compounds, including four polyaromatic hydrocarbons, by reversed phase high-performance liquid chromatography (HPLC). The analytical performance of the developed HS-SDME method was compared to the DLLME approach employing the same MILs. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Higher viscosity MILs have advantages in applications that require highly mechanically stable liquids. 29 Yoshida et al found that longer alkyl chain substituents in imidazolium-based MILs resulted in higher viscosity. 28 Other approaches for modulating the viscosity include mixing two components of different viscosity to generate mixtures that contain lower viscosity than the individual components themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Higher viscosity MILs have advantages in applications that require highly mechanically stable liquids. 29 Yoshida et al found that longer alkyl chain substituents in imidazolium-based MILs resulted in higher viscosity. 28 Other approaches for modulating the viscosity include mixing two components of different viscosity to generate mixtures that contain lower viscosity than the individual components themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the MIL was dispersed using acetone in combination with vortexing and subsequently collected using an external magnet. PAHs were back-extracted from the MIL using n-hexane, reconstituted in acetonitrile, and analyzed by HPLC with fluorescence detection to reveal that the [N 8 [98]. Relative to MIL-HS-SDME, MIL-DLLME required shorter extraction times and exhibited higher enrichment factors for nonvolatile compounds like acetophenone, 2-chloroaniline, and phenanthrene.…”
Section: Magnetic Ionic Liquids As Extraction Solvents In Dispersive mentioning
confidence: 99%
“…Furthermore, the magnetic rod also provides greater droplet stability relative to conventional syringes, thereby granting access to prolonged extraction times at faster stir rates. An and coworkers were the first to demonstrate MIL-based HS-SDME for the determination of aromatic compounds and PAHs [98]. By employing a rod magnet in the SDME method, it was possible to perform 60 min extractions at 400 or 800 rpm using the [P 6,6,6 4 2− ] MILs, respectively.…”
Section: Magnetic Ionic Liquids As Extraction Solvents For Single Dromentioning
confidence: 99%
“…proposed a microextraction method for analyzing acidic pharmaceuticals and phenolic compounds using MIL, which was recovered by an external magnetic field to avoid the use of volatile organic solvents or adsorbents. An et al . successfully used MIL as the extract solvent for the analysis of polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…In the separation field, Chatzimitakos et al 9 proposed a microextraction method for analyzing acidic pharmaceuticals and phenolic compounds using MIL, 9 which was recovered by an external magnetic field to avoid the use of volatile organic solvents or adsorbents. An et al 10 successfully used MIL as the extract solvent for the analysis of polycyclic aromatic hydrocarbons. Akbari et al 11 and Wang et al 12 also used MIL in the extraction and achieved good separation by a magnetic field.…”
Section: Introductionmentioning
confidence: 99%